Digitisation as a Contingent Factor in India's Financial Sector Development-growth Nexus: An Empirical Study. (August 2019) - Jayaraman, T. K.; Makun, Keshmeer
Financial sector development (FSD) has been recognised as a supportive factor, acting as a shift variable in the growth function, besides the fundamental variables of capital stock and labour. Since the beginning of the new millennium, rapid strides in the spread of information and communication technology (ICT) have enabled the hitherto reluctant, urban-based banking institutions to reach the rural masses for mobilising savings. Digitisation through various innovations has made it possible that 'brick and mortar less' bank branches now increasingly provide financial services to rural India. This study examines the role of digitisation as a contingent factor in India's FSD and growth nexus during the last 13 years (2003–2015). The findings of the empirical study through employment of ARDL methodology and application of bounds testing procedure by utilising 52 quarterly observations of the data series of relevant variables reveal that digitisation has indeed emerged a significant factor in the FSD and growth nexus, by playing a complementary role to FSD. There are two policy implications: (a) as ICT has emerged a major tool, it has to be supported at all levels, and (b) the financial inclusion process should be carried forward as it has all the potential to speed up economic growth and development. JEL: G21, O16, O33